2019
DOI: 10.3390/jimaging5110087
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Radar-Based Breast Imaging Algorithm Performance with Realistic Patient-Specific Permittivity Estimation

Abstract: Radar-based breast imaging has shown promise as an imaging modality for early-stage cancer detection, and clinical investigations of two commercial imaging systems are ongoing. Many imaging algorithms have been proposed, which seek to improve the quality of the reconstructed microwave image to enhance the potential clinical decision. However, in many cases, the radar-based imaging algorithms have only been tested in limited numerical or experimental test cases or with simplifying assumptions such as using one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…The above-mentioned comparison studies were carried out without considering the inter-patient variations in breast dielectric properties. Hence, in 2019 O'Loughlin et al tried to assess the impact of patient-specific permittivity estimation on beamformer comparison and found that DMAS can "improve" both healthy and abnormal images [135].…”
Section: Focusing Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above-mentioned comparison studies were carried out without considering the inter-patient variations in breast dielectric properties. Hence, in 2019 O'Loughlin et al tried to assess the impact of patient-specific permittivity estimation on beamformer comparison and found that DMAS can "improve" both healthy and abnormal images [135].…”
Section: Focusing Algorithmsmentioning
confidence: 99%
“…From the results reported by various research teams who compared the various focusing algorithms in radar imaging, DMAS is noted to have the most balanced performance and may be suggested as a suitable choice for future research efforts in this domain [132][133][134][135].…”
Section: Focusing Algorithmsmentioning
confidence: 99%
“…Let us assume B as all the points within the breast area and T as all the points located inside the target region. The following most commonly used metrics are investigated [9, 42]: The metric Δ: which is defined as the absolute distance between the real center of the tumor, T c and the predicted location of the tumor, which is estimated by the maximum energy on the reconstructed image I as following: …”
Section: Resultsmentioning
confidence: 99%
“…UWB microwave radar-based imaging technique (known as beamformers) rebuilds the image using the reflected wave from objects [82]. The radar system uses a UWB pulse from a transmit (TX) antenna to illuminate the breast, and the resulting reflections that are created at dielectrically differing tissue boundaries are collected by the receive (RX) components [83,84].…”
Section: Radar-based Techniquementioning
confidence: 99%